INFLUENCE OF USE APPROACH TO MATERIALS SCIENCE PROCESS SKILLS ON SKILLS CRITICAL THINKING STUDENT - Jaka Wijaya; Tri Jalmo; Rini Rita T. Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The observations and discussions with teachers who taught in Biology class III SD Negeri 1 Kampung Baru Lampung, it is known that the dominant learning more teachers using the conventional approach. Students also receive more information from the teacher so that students are less than optimal in empowering potential, including critical thinking skills. One effort that can help empower students in critical thinking skills is to use science process skills. The purpose of this study was to determine the effect of the use of science process skills for critical thinking skills of students in the subject matter of Characteristics and Needs of Living Things. The study design is a group pretest-posttest non-equivalent. The samples in this study were grade IIIA and IIIB were randomly selected by random sampling technique clusster. Data were obtained from the pretest and posttest at each meeting, the gain score is calculated by the formula. Data analysis using t-test at 5% level of belief using SPSS 17. The results of this study indicate that there is a significant effect of the use of science process skills for critical thinking skills of students in the subject matter of Characteristics and Needs of Living Things. Critical thinking skills students are learning in the classroom using science process skills approach higher grade than learning to use a conventional approach.